1979
DOI: 10.2134/agronj1979.00021962007100010021x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Size and Seeding Rate Effects upon Stand Density and Yield of Alfalfa1

Abstract: Legume seedlings from seed of different sizes compete with one another in pure seedings, usually to the detriment of smaller seedlings. We seeded variable rates of sized‐seed at Bozeman, Mont., to determine if less competition would permit lowering the seeding rate of alfalfa. We screened alfalfa (Medicago sativa L.) seed to small, medium, and large sizes weighing 160, 210, and 256 mg/100 seed respectively, and also made up a composite of the three sizes. We planted seed of each size at seeding rates of 1.1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 3 publications
3
14
0
1
Order By: Relevance
“…Sowing rate had the greatest effect on DM yield at the irrigated site with a range of 1-60 t ha" 1 between the lowest and highest sowing rates. Previous irrigated studies showed similar results in the sowing year; in Montana, DM yield increased 1-20 t ha" 1 with sowing rates ranging from 2-2 to 11-2 kg ha" 1 (Cooper et al 1979). In South Dakota, DM yield increased 1-10 t ha" 1 with sowing rates ranging from 4-5 to 17-9 kg ha" 1 (Hansen & Krueger 1973).…”
Section: Yieldsupporting
confidence: 54%
See 2 more Smart Citations
“…Sowing rate had the greatest effect on DM yield at the irrigated site with a range of 1-60 t ha" 1 between the lowest and highest sowing rates. Previous irrigated studies showed similar results in the sowing year; in Montana, DM yield increased 1-20 t ha" 1 with sowing rates ranging from 2-2 to 11-2 kg ha" 1 (Cooper et al 1979). In South Dakota, DM yield increased 1-10 t ha" 1 with sowing rates ranging from 4-5 to 17-9 kg ha" 1 (Hansen & Krueger 1973).…”
Section: Yieldsupporting
confidence: 54%
“…A quadratic effect may have been detected if higher sowing rates had been used. For example, other studies using higher sowing rates reported curvilinear responses in the first full-production year (Hansen & Krueger 1973;Cooper et al 1979). As observed for the sowing year, the slope of the line for the irrigated site was significantly (P < 001) lower than the slopes for the two dryland sites during the first fullproduction year (Fig.…”
Section: Plant Densitymentioning
confidence: 53%
See 1 more Smart Citation
“…This may be caused by non-uniform reduction in plant populations among cultivars. Plant losses were expected to be higher at higher seeding rates (Cooper et al 1979) because of winter injury, plant pests and diseases (Gossen et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…(5,9,11,16,18), sweet clover [Melilutus officinalis (L.) Lam.] (14), alfalfa (Medicago sativa L.) (7), and peanut (Arachis hypugaea L.) (13,17), In these studes larger seed size generally was associated with superior performance during emergence and subsequent development. However, this early-season benefit was not consistently reflected in yield.…”
mentioning
confidence: 86%